A ironia romântica da moda: o caso Alexander McQueen - Bruna Costa Nogueira (2024)
The aim of this proposal is to explore the relationships between romantic irony and allegory, which contribute to the construction of the designer Alexander McQueen’s aesthetic project. To do so, we emphasize how his creations incorporate the concept of allegory as proposed by Walter Benjamin, which deals with the relationships between symbols and their attributed or constructed meanings, collectively expressing a convention of meaning and also opening possibilities for being revisited and updated, being both ephemeral and fixed in time simultaneously. In addition to allegory, McQueen's creations relate to romantic irony, a movement that challenges and reformulates the way the author positions himself within the work and tends toward a greater capacity for self-critique within his artistic universe. This perspective is based on a playful attitude, which the author enjoys this game of construction/deconstruction and manipulation, a specific way of dealing with the boundaries of representation, that the author places himself in the work and conducts all possible games of dissimulation. Through the development of these relationships, it is possible to read McQueen's creations as expressions of an artistic language and understand that he uses fashion elements to give vent to an ironic critique of fashion, rather than occupying the common role of a vehicle for standardizing market trends. The idea of his ironic aesthetic project finds in the female representation, in the field of fashion, a crack through which it can infiltrate and flow through the system; he challenges conventional notions of femininity and questions these traditional expectations in fashion. He proposes a woman who stands out and is not willing to be just another domesticated figure. Instead, the designer proposes figures that exalt strength and ferocity, portraying his women as formidable beings who convey the message of not being easy prey but rather aposematic creatures, endowed with warnings of danger and toxicity to deter potential predators. To fully appreciate this work, I suggest you take the opportunity to learn Portuguese. After all, Brazil has a rich scientific production of high quality in our language, and learning Portuguese would be an elegant way to access this vast knowledge and strengthen cultural ties. Keywords: Alexander McQueen; Romantic Irony, Fashion, Allegory, Aposematism.